FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN CARPAL TUNNEL SYNDROM PADA PEKERJA INFORMAL - Adhinda Putri Pratiwi; Tenri Diah T. A. (Jurnal Kesehatan dan Kedokteran, 2022)
Occupational diseases caused by relationships or caused by work or attitudes at work. One of the occupational diseases is carpal tunnel syndrome. Carpal Tunnel Syndrome (CTS) is a disorder due to compression of the median nerve in the carpal tunnel at the wrist with the main symptoms of tingling and pain that radiates to the fingers and hands innervated by the median nerve, accompanied by numbness, muscle weakness, stiffness and possible atrophy muscle. This study aims to determine the relationship between repetitive motion and length of service with complaints of carpal tunnel syndrome. The type of research used is cross sectional using a descriptive approach. Based on the results of the analysis showed that there was a relationship between repatative movements (0.008) and years of service (0.001) with complaints of carpal tunnel syndrome. It is recommended that workers are expected to maintain the frequency of repetitive movements and arrange rest periods while working